A Multispectroscopic Study of 3 d Orbitals in Cobalt Carboxylates: The High Sensitivity of 2p3d Resonant X‐ray Emission Spectroscopy to the Ligand Field1. Issue 4 (6th December 2012) - van Schooneveld, Matti M.; Gosselink, Robert W.; Eggenhuisen, Tamara M.; Al Samarai, Mustafa; Monney, Claude; Zhou, Kejin J.; Schmitt, Thorsten; de Groot, Frank M. F.
<x xml:space="preserve">Abstract</x> d–d excitations in detail: High‐resolution 2p3d resonant X‐ray emission spectroscopy (RXES) allows the observation of more as well as more intense d–d excitations than UV/Vis spectroscopy does as demonstrated on cobalt(II) carboxylates. Together with ligand field multiplet (LFM) calculations this allows their detailed electronic structure description, while 2p X‐ray absorption spectroscopy (XAS) cannot discriminate these transition metal compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>